Action and Interaction: on the controllability of certain financial, social, and physical systems - Thamsten, Yuri (2024)
This thesis consists of contributions to the controllability of certain financial, social, and physical systems. The models widely vary amidst the problems we consider; some are stochas tic, other deterministic. Furthermore, we approach distinct problems using a large set of tools, ranging from calculus of variations, to dynamic programming, to nonlinear functional-analytic arguments. As a proper work in applied mathematics, we proceed with the conscientiousness that each body of theoretical advances is to be accompanied with corresponding numerical experiments.